The Regulation of DNA Damage Tolerance by Ubiquitin and Ubiquitin-Like Modifiers - Cipolla, Lina; Maffia, Antonio; Bertoletti, Federica; Sabbioneda, Simone (Frontiers in Genetics, 2016)
DNA replication is an extremely complex process that needs to be executed in a highly accurate manner in order to propagate the genome. This task requires the coordination of a number of enzymatic activities and it is incredibly fragile and prone to arrest after DNA damage. DNA damage tolerance provides a last line of defense that allows completion of DNA replication in presence of an unrepaired template. One of such mechanisms is called Post Replication Repair (PRR) and it is used by the cells to bypass highly distorted templates caused by damaged bases. PRR is extremely important for the cellular life and performs the bypass of the damage both in an error free and in an error prone manner. In light of these two possible outcomes, PRR needs to be tightly regulated and controlled in order to prevent accumulation of mutations leading ultimately to genome instability. Post-translational modifications provide the framework for this regulation and Ubiquitylation and SUMOylation of PRR proteins play a pivotal role in choosing which pathway to activate, controlling the different outcomes of damage bypass. PCNA (Proliferating Cell Nuclear Antigen), the DNA clamp for replicative polymerases, plays a central role in the regulation of damage tolerance and its modification by Ubiquitin and SUMO controls both the error free and error prone branches of PRR. Furthermore, a significant number of polymerases involved in the bypass of DNA damage possess domains that can bind post-translational modifications and they are themselves target for ubiquitylation. In this review, we will focus on how Ubiquitin and Ubiquitin-like modifications can regulate the DNA damage tolerance systems and how they are capable of controlling the recruitment of different proteins to the replication fork.